The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/app9153181
|View full text |Cite
|
Sign up to set email alerts
|

New Implant Macrogeometry to Improve and Accelerate the Osseointegration: An In Vivo Experimental Study

Abstract: A new implant design with healing chambers in the threads was analyzed and compared with a conventional implant macrogeometry, both implants models with and without surface treatment. Eighty conical implants were prepared using commercially pure titanium (grade IV) by the company Implacil De Bortoli (São Paulo, Brazil). Four groups were performed, as described below: Group 1 (G1), traditional conical implants with surface treatment; group 2 (G2), traditional conical implants without surface treatment (machined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 34 publications
(49 reference statements)
2
18
0
Order By: Relevance
“…PLLA is considered a gold standard for implantable synthetic polymers and does not degrade over the time frame of the in vivo studies (8 weeks), hence we selected it as a suitable control for this experiment. Moreover, the biocompatibility of nylons has long been established in a variety of different animal models 73,74 . Capsule formation in both species was found to be <200 µm and uncalcified, which indicated that no severe inflammatory response occurred as a consequence of the presence of the material and is within the range of an accepted response for an implantable material (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PLLA is considered a gold standard for implantable synthetic polymers and does not degrade over the time frame of the in vivo studies (8 weeks), hence we selected it as a suitable control for this experiment. Moreover, the biocompatibility of nylons has long been established in a variety of different animal models 73,74 . Capsule formation in both species was found to be <200 µm and uncalcified, which indicated that no severe inflammatory response occurred as a consequence of the presence of the material and is within the range of an accepted response for an implantable material (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Resonance frequency analysis (RFA) measurement using Osstell Mentor is frequently used to evaluate the implant stability in preclinical and clinical studies [32][33][34]. This technique has been widely used because it is not invasive and does not require extra procedures to obtain the data.…”
Section: Discussionmentioning
confidence: 99%
“…A similar mechanism has been proposed by other studies which show that bio-functionalised anodised layers (either macro or nano surfaced) have better resistance to corrosion and wear [209,280,292,306,307]. With regard to anodic layer performances for clinical translations, a better surface structuring strategy for Ti-based implants has been tested in vivo by Lotz et al [308] and Gehrke et al [309]. The study confirms that; (i) the micro/nano-structured/hydrophilic implants promotes the increased bone-to-implant contact and removal torque values in vivo and increased osteoblastic marker production in vitro compared to micro/hydrophilic or micro/nano-structured/hydrophobic implants, suggesting that osseointegration occurs in osteoporotic animals and that nano-structured surface properties improve the integration rate [308]; and (ii) implants with the new macrogeometry, which included healing chambers embedded within the threads, resulted in a significant increase in osseointegration, thereby facilitating better healing process ex vivo [309].…”
Section: Techniques To Enhance Mechanical Stability Of Anodic Tio 2 Layermentioning
confidence: 54%
“…With regard to anodic layer performances for clinical translations, a better surface structuring strategy for Ti-based implants has been tested in vivo by Lotz et al [308] and Gehrke et al [309]. The study confirms that; (i) the micro/nano-structured/hydrophilic implants promotes the increased bone-to-implant contact and removal torque values in vivo and increased osteoblastic marker production in vitro compared to micro/hydrophilic or micro/nano-structured/hydrophobic implants, suggesting that osseointegration occurs in osteoporotic animals and that nano-structured surface properties improve the integration rate [308]; and (ii) implants with the new macrogeometry, which included healing chambers embedded within the threads, resulted in a significant increase in osseointegration, thereby facilitating better healing process ex vivo [309]. In addition, Yi et al [310] reported that the treated Ti-implant surface with TNTs of different diameters (30 nm, 50 nm, 70 nm, and 100 nm) showed that the highest mean new bone area and the highest mean of removal torque value were observed in 30 nm experimental group and in 70 nm experimental group at 2 weeks and 6 weeks in vivo, respectively.…”
Section: Techniques To Enhance Mechanical Stability Of Anodic Tio 2 Layermentioning
confidence: 99%
See 1 more Smart Citation